(untitled) (Dristikon: A Multidisciplinary Journal, 2023)
This article, as the statement of the problem, raises the question of whether the Limburaditional song Palam cultivates and instils useful knowledge and skills in practical life. In order to acquire the answer, this article has set the objective to find out the pragmatic values that the Palam song has in the Limbu ethnic community. The article, being descriptive in design, has readily made use of description as its pattern of development. It has used the qualitative research technique which is based on unstructured, non-numerical data drawn from related books, journals, research theses, or Online resources. The song Palam is concerned with ethnic as well as cultural issues, and for this reason, the article has chosen the ethnocultural theory which deals with ethnic identity-based cultural practices, traditional customs, and social behaviour. The theory also refers to a group of people who have a belief that they are ethnically and culturally divergent from other groups or communities. The analysis has revealed that the folk-song Palam has long been tacitly inculcating very significant as well as useful knowledge and skills to the community even though certain native individuals find it of no use at all. From this article, it is fairly expected that interested individuals and anthropologists can acquire specific insights from the Limbu culture and traditional song Palam.